2013
DOI: 10.1007/s12350-013-9765-4
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of transient ischemic dilatation with otherwise normal SPECT myocardial perfusion imaging: A cautionary note in patients with diabetes and coronary artery disease

Abstract: This study confirms a benign prognosis of TID with otherwise normal MPI in patients without diabetes or CAD, but cautions against extending this conclusion to high-risk individuals, particularly those with diabetes or CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…8,9 In Table 1, it can be seen that normal cutoff values obtained by Jameria et al are in fact remarkably similar to the values reported for exercise or pharmacological stress obtained with conventional imaging systems, including one previous report of TID in patients imaged in upright position. 10 Similar to previous reports, the threshold defined as 2 standard deviations (SD) above the mean is indeed higher for the pharmacological stress studies than for the exercise studies. When comparing these recent reports, one can appreciate that there are several potential factors affecting the value of the normal threshold, such as imaging protocol, patient position, normal population definition, statistical threshold definition, and software used for TID computation.…”
Section: Introductionsupporting
confidence: 82%
“…8,9 In Table 1, it can be seen that normal cutoff values obtained by Jameria et al are in fact remarkably similar to the values reported for exercise or pharmacological stress obtained with conventional imaging systems, including one previous report of TID in patients imaged in upright position. 10 Similar to previous reports, the threshold defined as 2 standard deviations (SD) above the mean is indeed higher for the pharmacological stress studies than for the exercise studies. When comparing these recent reports, one can appreciate that there are several potential factors affecting the value of the normal threshold, such as imaging protocol, patient position, normal population definition, statistical threshold definition, and software used for TID computation.…”
Section: Introductionsupporting
confidence: 82%
“…A post-stress left ventricular ejection fraction of 50% or more was considered normal. The transient ischemic dilation ratio, a marker for high-risk scan, was tabulated (16).…”
Section: Stress Mpimentioning
confidence: 99%
“…Two multivariable logistic regression models were fit to calculate the predicted probability of MACE (model 1) or revascularization within 6 mo (model 2) as determined by established clinical and imaging predictors (independent variables) known to affect these outcomes (1,9,12,16). The calculated probabilities of MACE were then annualized.…”
Section: Determination Of Predicted Probability Of Outcome Eventsmentioning
confidence: 99%
“…Importantly, abnormal TID predicted higher event rate even among patients with normal or mildly abnormal perfusion, particularly among patients with diabetes mellitus. 17 In addition to TID, several imaging findings have been used as markers of extensive CAD. During the early 1980's increased post-stress lung uptake of thallium-201 on MPI has been shown to correlate with severe CAD and left ventricular dysfunction.…”
mentioning
confidence: 99%